Pengaruh Pelaksanaan Program P5 dan Budaya Sekolah Terhadap Kedisiplinan Siswa di SMP Negeri 8 Palembang - Nina Veranica; Tri Widayatsih; Sri Wahyu Indrawati (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to determine the effect of the implementation of the P5 program and school culture on student discipline at SMP Negeri 8 Palembang. This type of research is quantitative research. The sample in this study was 185 students of SMP Negeri 8 Palembang. Data collection techniques used questionnaires. Data analysis techniques used quantitative descriptive analysis techniques, simple regression and multiple regression tests. The results of this study state that 1) there is a significant effect of the implementation of the P5 program on student discipline at SMP Negeri 8 Palembang; 2) there is a significant effect of school culture on student discipline at SMP Negeri 8 Palembang 3) there is a significant effect together of the implementation of the P5 program and school culture on student discipline at SMP Negeri 8 Palembang